Understanding the surge in elective caesarean sections: Role of older women's childbirth choices on younger women in India - Priyanka Dixit; Anjali Bansal; Rahul Mishra; Eugine Paul; Shivalingappa S. Halli (Global Transitions, 2025)
The global rise in Caesarean sections (CS), including India's increase from 8.5 % in 2005-06 to 21.5 % in 2019–21, poses a significant public health challenge. This study investigates the factors driving elective CS decisions, focusing on how older women's childbirth experiences influence younger women's choices within the same household, using data from the National Family Health Survey-5. Multivariable logistic regression and propensity score matching (PSM) were applied to see the influence of older women's Elective CS decisions on their younger peers within the same household. Results show that younger women were more likely to choose elective CS if older women previously had one (29.0 % vs. 15.1 %, AOR = 1.72). Other significant predictors include mass media exposure (AOR = 1.13), private healthcare (AOR = 2.84), and older maternal age (AOR = 2.54 for ages 35–40 years). Regional differences were evident, with South India showing the highest CS rates among younger women (40.4 %), when their older household peer had undergone a CS rates. Wealth and education also played a role, with the richest women having higher odds (AOR = 2.00) and secondary education showing the greatest effect (AOR = 1.43). PSM analysis found an eight percent higher likelihood of elective CS among younger women if older women had one (ATT = 0.086; p < 0.001). In conclusion, the study shows that the childbirth experiences of older women strongly affect younger women's decisions to opt for elective CS, highlighting the important role of influence within households in shaping these choices.